Supervisi Coaching: Peningkatan Kinerja Mengajar Guru - Maria Ulfah; Ahmad Noviansah (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2020)
The weak teaching performance of teachers that resulted from the less precise pattern of the head of the Madrasah. In some madrasahs, the headmaster never gave a structured guide to the teacher. This research aims to see the application of guidance with the method of coaching by the head of Madrasah in increasing the performance of teachers in teaching. This study uses a qualitative approach with a descriptive method. Data collection techniques are conducted through observation and documentation. The research subject is the head of the Madrasah, and 12 teachers from 6 (six) Madrasah Ibtidaiyah in the city of Semarang, namely MI Hasanuddin, MI Tawang, MI Gisikdrono, MI Al Amin, MI Kebonharjo, and MI Mirfaul Ulum, each Madrasah 2 teachers, one from high class and one from low grade. The results showed that the teaching performance of all studied teachers had increased. Can be seen from the observation of the implementation of supervision by the principal after being given coaching with the method of coaching